1977
DOI: 10.1007/bf01078356
|View full text |Cite
|
Sign up to set email alerts
|

Phlegmonous gastritis diagnosed by endoscopic snare biopsy

Abstract: A case of phlegmonous gastritis, diagnosed for the first time without laparotomy and with spontaneous recovery, is described. The only procedure allowing nonsurgical diagnosis of this disease is endoscopic snare ("jumbo") biopsy of the giant folds in the diseased parts of the stomach. Snare biopsy includes submucosal tissue which is the main site of histological changes in phlegmonous gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The disease is often confused with infiltrating gastric carci− noma (Borrmann type IV) [8], and differentiating the two dis− eases is very difficult. Phlegmonous gastritis can be diagnosed by endoscopic snare biopsy without gastrectomy [9]. Microscop− ically, there is an infiltration of polymorphonuclear leukocytes in the submucosa and necrotic mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is often confused with infiltrating gastric carci− noma (Borrmann type IV) [8], and differentiating the two dis− eases is very difficult. Phlegmonous gastritis can be diagnosed by endoscopic snare biopsy without gastrectomy [9]. Microscop− ically, there is an infiltration of polymorphonuclear leukocytes in the submucosa and necrotic mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…However it is noteworthy that even without such apparent underlying conditions, phlegmonous gastritis develops after endoscopic procedures. Bron et al reported on a patient who developed phlegmonous gastritis after endoscopic snare biopsy [Bron et al 1977]. Another case of phlegmonous gastritis after endoscopic mucosal resection (EMR) of smaller size that required total gastrectomy has been reported [Lee et al 2005].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is often difficult to diagnose them during endoscopy because the inflammation involves predominantly the submucosa. 3 We report the endosonographic and endoscopic findings in a case of phlegmonous gastritis.…”
Section: Received 27 June 2006; Accepted 6 January 2007mentioning
confidence: 98%